Tahap komunikasi dalam Bahasa Arab dalam kalangan pelajar Sarjana Muda Bahasa Arab di IPTA Malaysia - Abdul Halim Mohamad (2009)
The purpose of this study was to investigate the using of Arabic among the students of Bachelor of Arabic at the Local Higher Institutions (IPTA) and to find out the reasons which obstruct the using of Arabic among them. The research has been carried out among 130 students of Bachelor of Arabic at the Local Higher Institutions (UPM, UKM, UM, UIAM, and USIM. The results shown the level of using Arabic among the students of Bachelor of Arabic at IPTA either in the classroom or out-site classroom is low and did not satisfied. This is because of the external and internal factors. The internal factors are the feelings of students toward the Arabic language such as shy, not confident, afraid, not courageous, ect. The results of this research may affect the implication practical of technique and method of teaching of Arabic in order to uplift the using of Arabic among the Arabic Bachelor students.